2010
DOI: 10.1007/s11104-010-0568-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among main soil properties and three N availability indices

Abstract: A biological (3 and 6 weeks aerobic incubation) and a chemical method [successive extractions with cold 0.1 (H1-N) and 0.5M HCl (H2-N)] were applied to 21 soils to determine: a) the potentially mineralizable-N; b) the most useful soil variables for predicting soil-N availability; and c) their usefulness for predicting N uptake by a greenhouse wheat crop. At t= 3, both net N mineralized (NNM) and net N mineralization rate (NNMR) were correlated: a) positively with SOM-and CEC-related variables; and b) positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
(78 reference statements)
1
4
0
Order By: Relevance
“…The higher inorganic N content and six-time higher NH 4 + /NO 3 ratio in the burnt soil right after the fire is in agreement with the widely reported increased soil inorganic N concentrations after fire [see Wang et al (2014) and references therein], especially that of NH 4 + , a direct product of combustion, whereas NO 3 requires nitrification to be formed (Karhu et al, 2015). In incubation experiments without plants and under optimal conditions for N mineralisation, in which N losses are largely reduced, an increase in inorganic N concentration is usually reported (Abadín et al, 2011). In US, the sustained parallel increase in both NH 4 + and NO 3 and the rather stable NH 4 + /NO 3 -ratio during the whole experiment suggested that both net mineralization and net nitrification were fairly constant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The higher inorganic N content and six-time higher NH 4 + /NO 3 ratio in the burnt soil right after the fire is in agreement with the widely reported increased soil inorganic N concentrations after fire [see Wang et al (2014) and references therein], especially that of NH 4 + , a direct product of combustion, whereas NO 3 requires nitrification to be formed (Karhu et al, 2015). In incubation experiments without plants and under optimal conditions for N mineralisation, in which N losses are largely reduced, an increase in inorganic N concentration is usually reported (Abadín et al, 2011). In US, the sustained parallel increase in both NH 4 + and NO 3 and the rather stable NH 4 + /NO 3 -ratio during the whole experiment suggested that both net mineralization and net nitrification were fairly constant.…”
Section: Discussionsupporting
confidence: 89%
“…We are aware of the potential limitations of such an experimental design as it precludes some processes which play an important role in N cycling (physical mixing of soil and straw, plant growth, variable weather conditions). Nonetheless, short-or medium-term incubations are still considered an adequate method to get a picture of the potential capability of the different soils to transform N under optimal conditions [see Abadín et al (2011) and references therein] and to test the effects of straw on soil N cycling. With the wetting system described in Gómez-Rey & González-Prieto (2013), which allows easily wetting highly hydrophobic soils, the soils were humidified to slightly below 70% of their WHC before starting the preincubation, so when soils received the labelled solution for the tracing experiment they were at 70% of their WHC.…”
Section: Soil Incubation and Gross N Transformation Ratesmentioning
confidence: 99%
“…Herbivores (Aranibar et al, 2008;Craine et al, 2009a;Frank and Evans, 1997;Frank et al, 2000) and soil properties (Abadín et al, 2010) have often been shown to impact soil d 15 N, which is an indication of modifications of nitrogen cycling. In particular, herbivores impact nitrogen cycling and abovegroundebelowground linkages both directly through changes in plant growth and physiology and alterations of the quality and quantity of mineral and organic resources and, indirectly, through changes in the functional composition of vegetation (Bardgett and Wardle, 2003).…”
Section: Impact Of Soil and Herbivores On D 15 Nmentioning
confidence: 99%
“…In turn, the modification of these fluxes impacts 15 N signatures and may either increase (Frank and Evans, 1997) or decrease (Frank et al, 2000) soil 15 N abundances. Similarly, soil properties such as soil depth, soil compaction, soil texture or soil organic matter content are likely to impact biomass and soil 15 N signatures (Abadín et al, 2010) through their effects on soil capacity to retain mineral nutrients, or through their effects on microbial biomass and activities.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate organic matter N (POM-N) and pH explained 18% and 25%, respectively, of the variability in the first 2 weeks of aerobic incubation. Moreover, Abadín, González-Prieto [ 17 ] studied 21 soil samples and pointed out that H + , Ca 2+ , K + of cation exchange capacity (CEC), the sum of CEC-bases (S CEC ), total CEC (T CEC ) and soil δ 15 N value are closely correlated with nitrogen mineralization, respectively, after aerobic incubation 3 weeks and 6 weeks.…”
Section: Introductionmentioning
confidence: 99%